Type 1 diabetes incidence increased during the COVID-19 pandemic years 2020-2021 in Czechia: Results from a large population-based pediatric register - Cinek, Ondřej; Slavenko, Matvei; Pomahačová, Renata; Venháčová, Petra; Petruželková, Lenka; Škvor, Jaroslav; Neumann, David; Vosáhlo, Jan; Konečná, Petra; Kocourková, Kamila; Strnadel, Jiří; Průhová, Štěpánka; et al. (Pediatric diabetes, 2022)
BACKGROUND: To explore type 1 diabetes incidence patterns during the pandemic years 2020 and 2021 in Czechia, to compare them to the trends from the previous decade, and to test its association with indicators of containment measures and of pandemic severity (school closing and the all-cause excess mortality). METHODS: The Czech Childhood Diabetes Register is a population-based incidence register recording patients age 0-14.99 years at diabetes onset. Type 1 diabetes incidence in the pandemic period (April 2020-end of observation Dec 2021) was compared by Poisson regression models to the incidence patterns over the past decade 2010-2019. RESULTS: During the pandemic years 2020-2021, 956 children 0-14.99 years old manifested with type 1 diabetes in Czechia. The observed incidence (27.2/100,000/year) was significantly higher than what was expected from the trends over 2010-2019 (incidence rate ratio, IRR = 1.16, 95%CI 1.06-1.28, p = 0.0022). The incidence had a trough during the first lockdown (March-May 2020), then it rose above expected values with no usual summer decrease. The assessed pandemic indicators (school closing and all-cause excess mortality) were not associated with the incidence levels. CONCLUSIONS: The COVID-19 pandemic was associated with a notable upward inflection of the type 1 diabetes incidence curve; the early months of the first lockdown were however hallmarked by a significant dip in new diabetes diagnoses. Long-term observation will show whether the increased incidence originated only from accelerating an advanced preclinical Stage 2 to overt diabetes, or whether the pandemic triggered new cases of islet autoimmunity.
Keywords: dítě; Česká republika; novorozenec; Adolescent; pandemie; předškolní dítě; lidé; Communicable Disease Control; Incidence; Czech Republic; kojenec; diabetes mellitus 1. typu; Pandemics; COVID-19; Humans; Child; kontrola infekčních nemocí; Infant, Newborn; Infant; incidence; Diabetes Mellitus, Type 1; Child, Preschool; mladiství